2017
DOI: 10.21037/acs.2017.09.10
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcomes of transcatheter aortic valve implantation (TAVI): a systematic review of 5-year survival and beyond

Abstract: Background: Transcatheter aortic valve implantation/replacement (TAVI/TAVR) is becoming more frequently used to treat aortic stenosis (AS), with increasing push for the procedure in lower risk patients.Numerous randomized controlled trials have demonstrated that TAVI offers a suitable alternative to the current gold standard of surgical aortic valve replacement (SAVR) in terms of short-term outcomes. The present review evaluates long-term outcomes following TAVI procedures.Methods: Literature search using thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 74 publications
3
64
1
5
Order By: Relevance
“…A report from 5-year follow-up from PARTNER I trial revealed excellent durability without significant structural valve degeneration up to 5 years [24]. A meta-analysis confirmed the good long-term durability of TAVR devices [25]. However, the long-term durability is of pivotal importance in younger patient with a life-expectance greater than 10 years when TAVR or SAVR options are considered.…”
Section: Discussionmentioning
confidence: 98%
“…A report from 5-year follow-up from PARTNER I trial revealed excellent durability without significant structural valve degeneration up to 5 years [24]. A meta-analysis confirmed the good long-term durability of TAVR devices [25]. However, the long-term durability is of pivotal importance in younger patient with a life-expectance greater than 10 years when TAVR or SAVR options are considered.…”
Section: Discussionmentioning
confidence: 98%
“…Так, во французском регистре PMSI, включившем 1332 пациента, частота летальных исходов на госпитальном этапе составила 7,9% [12]. В регистре Swiss TAVI данный показатель составил 4,8% [13]. Различия в летальности могут объясняться как характеристикой пациентов (сопутствующая патология и так называемый индекс "дряхлости"), так и особенностями процедуры (операционный доступ, тип имплантируемого протеза).…”
Section: Discussionunclassified
“…Os resultados clínicos no curto prazo são satisfatórios (MCRAE; RODGER, 2012) e a melhora na qualidade de vida é significativa (WONG; GREEN; WILLIAMS, 2013). Apesar de ainda ser necessária a consolidação dos resultados clínicos do TAVI em médio e longo prazo, alguns estudos já têm constatado bons índices de sobrevida entre o terceiro e quarto ano após o tratamento em pacientes idosos (CHAKOS et al, 2017; KOURKOVELI; SPARGIAS; HAHALIS, 2018).…”
Section: Conclusãounclassified